Exploring stress coping strategies, motivation, and academic achievement of orphaned adolescents - Minaldo, Regina Salve R.
This qualitative study explored the resilience factors which contributed to the academic achievements of orphaned adolescents in Ellah Yallah Home of Virlanie Foundation. It attempted to determine the stress, coping strategies, motivations, and academic achievements indicated by grades of a purposive sample often adolescents ages 12 to 15 years old. Data was gathered in one week using adolescents' interviews, key informants' interviews, and visit anecdotes. Findings reveal that the adolescents were experiencing various stressors in relation to their academics emanating from the school, the home, interpersonal relationships and the self. The respondents coped through various ways, mainly by seeking social support and relaxation, followed by focusing on solving the problem, keeping to self, worrying ignoring the problem, or seeking psychological support. Motivations of the orphaned adolescents in their studies were found to be highly extrinsic, coming from the foundation, the school, and the biological family. Finally, half of the respondents were academically struggling, having final grade averages below 79, while the other half were academically-resilient, getting final grade averages of 80 and above. Based from the results, the role of the environment, comprised by the foundation, home, and school, is given critical importance in helping the orphaned adolescents with study pressures. It is recommended to develop resilience not only among the youngsters but also in the caring environment to better facilitate their academic performances. Finally, a longitudinal study or a bigger sample of orphaned children and adolescents would explore of the academic resilience phenomenon.